POSTURE RELATED MUSCULOSKELETAL DISORDERS AMONG NURSING STAFF IN A TERTIARY CARE HOSPITAL - Sandeep, Narwane; Pranjal A, P Sharma (International Journal of Clinical and Biomedical Research, 2017)
Background: Work-related musculoskeletal disorders are the most common occupational health problems in developing countries. The present study was conducted with an aim to study prevalence and cause of musculoskeletal disorders in nurses. Method: It was a cross sectional study. 103 nurses were included in the study. and were asked to answer a well-equipped questionnaire so as to obtain information about their postural habits and other daily activities. Results: Among the nurses, 86% were found to be suffering from MSDs, low back pain and leg pain being the commonest problems. 30% of the nurses took medications for the pain. 52% required work related weight lifting activity. Out of those requiring weight lifting activity, only 48% of the nurses acquired proper posture (squatting without bending forward) while lifting weight. Mere 26% of the nurses acquired proper erect posture while sitting. Only 20% of them supported the lower back while sitting. 66% of the nurses did not perform any physical activity during the break. 56% of the nurses had not attended any workshop on good postural habits and had no idea about the ergonomically correct postures. However, no association was found between the postural habits of nurses and prevalence of Musculoskeletal disorders. Conclsuion: In view of high prevalence and insufficient knowledge and practice of ergonomics, it is the need of the hour to educate the nurses about the ergonomically correct postural habits and further complications. KEY WORDS: Ergonomics; Musculoskeletal disorders; Nursing staff; Posture.